Peranan Komunikasi Dalam Sistem Sosial : Analisis Teori Niklas Lukman - Handayani, Difha Sulistyawati (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
The theory of communication as autopoiesis proposed by Niklas Luhmann offers a revolutionary perspective in understanding communication in social systems. Luhmann argues that communication is not just a tool for exchanging information, but is an independent process and has autonomous mechanisms to maintain and reproduce itself. This theory combines the concept of autopoiesis which originally came from biology, where a system can produce and maintain its own components through internal interactions. In Luhmann's theory, communication is seen as a basic element of a social system that has the ability to create and reproduce social structures through processes communication itself. Luhmann emphasized that communication occurs through three main elements: information, message, and understanding. This process not only transmits information, but also shapes and constructs social reality. Communication in Luhmann's view is a selective process that involves selecting the information to be communicated, the way the information is conveyed, and how the information is understood by the recipient. Apart from that, the theory of communication as autopoiesis is relevant in the context of modern communication which is increasingly complex and fragmented. In the digital era, where information spreads rapidly and in large quantities, understanding communication as an autopoietic process helps us understand how information is processed, selected, and internalized in social systems. It also helps in understanding the challenges and opportunities that have arisen from developments in communication technologies, such as social media and the internet, which have changed the way we communicate and interact with each other. Overall, Niklas Luhmann's theory of communication as autopoiesis provides a powerful theoretical framework for understanding communication as an independent and dynamic process in social systems. This theory not only provides insight into how communication functions in a social context, but also offers analytical tools for exploring the complexity and dynamics of communication in modern society. By understanding communication through the lens of autopoiesis, we can better capture the essence of the communication process and how it shapes our social reality.